'No peace, no war' proponents? How pro-regime militias affect civil war termination and outcomes. (March 2019) - Aliyev, Huseyn
Previous research on non-state actors involved in civil wars has tended to disregard the role of extra-dyad agents in influencing conflict outcomes. Little is known as to whether the presence of such extra-dyadic actors as pro-regime militias affects conflict termination and outcomes. This article develops and tests a number of hypotheses on the pro-government militias' effect upon civil war outcomes. It proposes that pro-regime militias involved in intrastate conflicts tend to act as proponents of 'no peace, no war', favouring low-activity violence and ceasefires over other conflict outcomes. These hypotheses are examined using an expanded dataset on pro-government militias and armed conflict in a statistical analysis of 229 civil war episodes from 1991 to 2015. These findings shed new light on the role of extra-state actors in civil wars.